Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the equation [tex]\(\cot B = \sqrt{\frac{x+4}{x-4}}\)[/tex] for [tex]\(x\)[/tex], follow these steps:
1. Square both sides to eliminate the square root:
[tex]\[ \cot^2 B = \left(\sqrt{\frac{x+4}{x-4}}\right)^2 \][/tex]
Simplifying the right side, we get:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
2. Isolate the fraction involving [tex]\(x\)[/tex]:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
Multiply both sides by [tex]\(x-4\)[/tex] to get rid of the denominator:
[tex]\[ \cot^2 B \cdot (x - 4) = x + 4 \][/tex]
3. Distribute [tex]\(\cot^2 B\)[/tex] on the left side of the equation:
[tex]\[ \cot^2 B \cdot x - 4 \cot^2 B = x + 4 \][/tex]
4. Move all terms involving [tex]\(x\)[/tex] to one side and constants to the other:
[tex]\[ \cot^2 B \cdot x - x = 4 + 4 \cot^2 B \][/tex]
Factor [tex]\(x\)[/tex] out of the left side:
[tex]\[ x (\cot^2 B - 1) = 4 (1 + \cot^2 B) \][/tex]
5. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{4 (1 + \cot^2 B)}{\cot^2 B - 1} \][/tex]
Now, by using the trigonometric identity [tex]\(\cot^2 B + 1 = \csc^2 B\)[/tex], we get:
[tex]\[ 1 + \cot^2 B = \csc^2 B \][/tex]
Substituting this into our equation for [tex]\(x\)[/tex], we get:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
Thus, the solution for [tex]\(x\)[/tex] in terms of [tex]\(B\)[/tex] is:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
This is the value of [tex]\(x\)[/tex] that satisfies the given equation [tex]\(\cot B = \sqrt{\frac{x+4}{x-4}}\)[/tex].
1. Square both sides to eliminate the square root:
[tex]\[ \cot^2 B = \left(\sqrt{\frac{x+4}{x-4}}\right)^2 \][/tex]
Simplifying the right side, we get:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
2. Isolate the fraction involving [tex]\(x\)[/tex]:
[tex]\[ \cot^2 B = \frac{x+4}{x-4} \][/tex]
Multiply both sides by [tex]\(x-4\)[/tex] to get rid of the denominator:
[tex]\[ \cot^2 B \cdot (x - 4) = x + 4 \][/tex]
3. Distribute [tex]\(\cot^2 B\)[/tex] on the left side of the equation:
[tex]\[ \cot^2 B \cdot x - 4 \cot^2 B = x + 4 \][/tex]
4. Move all terms involving [tex]\(x\)[/tex] to one side and constants to the other:
[tex]\[ \cot^2 B \cdot x - x = 4 + 4 \cot^2 B \][/tex]
Factor [tex]\(x\)[/tex] out of the left side:
[tex]\[ x (\cot^2 B - 1) = 4 (1 + \cot^2 B) \][/tex]
5. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{4 (1 + \cot^2 B)}{\cot^2 B - 1} \][/tex]
Now, by using the trigonometric identity [tex]\(\cot^2 B + 1 = \csc^2 B\)[/tex], we get:
[tex]\[ 1 + \cot^2 B = \csc^2 B \][/tex]
Substituting this into our equation for [tex]\(x\)[/tex], we get:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
Thus, the solution for [tex]\(x\)[/tex] in terms of [tex]\(B\)[/tex] is:
[tex]\[ x = \frac{4 \csc^2 B}{\cot^2 B - 1} \][/tex]
This is the value of [tex]\(x\)[/tex] that satisfies the given equation [tex]\(\cot B = \sqrt{\frac{x+4}{x-4}}\)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.